Piety and power: Muslims and Christians in West Africa - Sanneh, Lamin O. (Faith meets faith series, 1996)
Providing a unique perspective on historical patterns of religious interaction in West Africa and their meaning for world Christianity and Islam today, this book places the inner-faith issues firmly in an African social setting. Sanneh explores the impact of Islam, Christianity and European mission and colonialism in terms of African adaptations and expressions.